Teachers' beliefs about teaching and learning and their implications for meaningful learning practices in elementary school in Bandung: a phenomenological study - Fransiskus Ransus; Verawaty Sinaga; Agrielsa Alphasati Sinaga; Christina Ester Manthalina Hutabarat (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to explore teachers' beliefs and their implications for meaningful learning practices in elementary schools using a qualitative phenomenological approach. The participants consisted of ten elementary school teachers in Bandung, Indonesia, from both public and private schools, who were purposively selected based on the criteria that (a) they are recognized as highly dedicated teachers and (b) they have more than ten years of teaching experience. Data were collected through interviews, observations, and document analysis, and subsequently analyzed and categorized into thematic findings. The results reveal several patterns related to teachers' beliefs, including (1) teacher–student relationships as the foundation of learning, (2) knowledge construction through connecting new learning with students' prior experiences to promote meaningful learning, (3) teachers' flexibility in adapting instructional strategies to students' needs, (4) teachers' positive beliefs about the potential of every student, and (5) teachers' beliefs as a driver of instructional innovation. These findings indicate that meaningful learning is shaped not only by the strategies employed but also by the beliefs that underpin teachers' pedagogical practices. This study contributes to strengthening the role of teacher beliefs as a bridge between pedagogical knowledge and classroom practice. Practically, the findings may serve as a foundation for teacher professional development that focuses not only on technical competencies but also on reflective beliefs as a basis for pedagogical practice.